Chlorophylla Fluorescence Imaging Technique for Fresh Quality Assessment of Tomato and Pepper FruitsStoredUnder Different Conditions (JOURNAL OF ADVANCES IN AGRICULTURE, 2014)
The objective of this study was to find a rapid determination of the freshness of tomato (Solanum lycopersicum L.) and pepper (Capsicum annuum L.)fruits using portable chlorophyll fluorescence imaging instrument. To assess the fresh quality of tomato and pepper fruits, an imaging anlaysis of the photochemical responses of pericarp or exocarp of tomato and pepper fruits was performed with fruits preserved under the different storage conditions. The observed chlorophyll imaging photos were numerically transformed to the photochemical parameters on the basis of chlorophyll fluorescence.The storage conditions for fruits were regulated as follows; room temperature (control), heat (42°C), wet (25°C and 80% relative humidity), and chilling (4°C) conditions.Chlorophyll fluorescence imaging (CFI) method showed that the decrease in Fv/Fmratios of pepper fruits was lower at room temperatureand under wet condition than the other conditions. Although Fv/Fmratios and Î¦PSII values in tomato fruits showed low fluorescence responses, the changing patterns have permitted to determine th freshness. In heat condition, the photochemical parameters calculated from the images of Fv/Fm ratios, Î¦PSII and non-photoquenching (NPQ) were also available to determine the freshness of fruits. In our study, it was clearly indicated that the chillingcondition was the suitable condition for thelong storage of tomato and pepper fruits. The CFI analysis is applicable as a rapid screening method for the determination of freshness of tomato and pepper fruits.